Application of TTSP to non-linear deformation in composite propellant. Issue 1 (2nd January 2018) - Jinsheng, Xu; Hongli, Wang; Xiaohong, Yang; Long, Han; Changsheng, Zhou
Abstract : A series of constant-rate tensile tests and relaxation tests were conducted to assess the mechanical properties of the hydroxy-terminated polybutadiene (HTPB) propellant. The relaxation modulus master curve was acquired using relaxation tests at the linear viscoelastic segment, and stress-reduced time master curves at different strain levels were established to determine whether the time–temperature superposition principle (TTSP) could be used to assess the non-linear mechanical property of the HTPB propellant. Results showed that the mechanical properties of HTPB propellant strongly depend on temperature; the extent of this dependence is enhanced with decrease in temperature, and the TTSP can be used in non-linear segments. With the application of the TTSP, the ultimate strength and the stress–strain curves of constant-rate tensile tests can be predicted at any temperature and strain rate, and the predicted σ – ε responses matched the test results closely, but led to some errors at high temperatures, this is because of some errors in the time–temperature shift factors.